Development of arm and leg for seabed walking robot CRABSTER200. (1st April 2016) - Shim, Hyungwon; Yoo, Seong-yeol; Kang, Hangoo; Jun, Bong-Huan
Abstract: This paper presents the development of arm and leg of seabed walking robot named CRABSTER200 (CR200) for precise seabed exploration and underwater works in coastal area with strong tidal current. For seabed walking and precise underwater works, CR200 uses six legs and front two legs can be transformed to manipulators. In order to design robotic arm and leg, the parameters such as the degree of freedom (D.O.F), dimensions, motion range, joint structure, and mass are determined. Then, suitable joint actuators and reduction gears are selected through a simple force analysis. In addition, a communication method between legs and main controller, actuator controllers, and sensors are selected. The detailed mechanical design for 200 m class pressure–resistance as well as watertight is performed. Also, the arms and legs are built by assembled fabricating the mechanical parts. Finally, in order to verify the performance of the arm and leg, the watertight test with 25 bar pressure–resistance and joints operating test through posture control of CR200 are performed. This paper describes the whole design and implementation process of the underwater robotic arm and leg of the seabed robot CR200. Highlights: We develop underwater arm and leg of seabed walking robot CRABSTER200. CRABSTER200 uses six legs during walking and front two legs as manipulators during underwater work. We design link and joint system with 200 m class pressure–resistance and watertight. Developed arm and leg have the sufficient performance for underwater work and seabed walking.